2007
DOI: 10.1017/s1355617707071214
|View full text |Cite
|
Sign up to set email alerts
|

fMRI detection of early neural dysfunction in preclinical Huntington's disease

Abstract: Neuropsychological and neuroimaging changes have been observed in individuals with the Huntington's disease (HD) gene expansion prior to the onset of manifest HD. This cross-sectional fMRI study of preclinical HD (pre-HD) individuals was conducted to determine if functional brain changes precede deficits in behavioral performance and striatal atrophy. Twenty-six pre-HD and 13 demographically matched healthy participants performed a time reproduction task while undergoing fMRI scanning. Pre-HD participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 50 publications
(69 reference statements)
8
94
1
1
Order By: Relevance
“…Indeed, cross-sectional and longitudinal MRI studies have suggested that structural brain changes in carriers of the HD mutation may serve as biomarkers and potentially as surrogate endpoints in clinical trials [2,3,4,5,6]. However, intact brain structure in preHD has also been reported [7,8,9,10]. It is unlikely that these discrepancies can be solely explained by differing sample sizes, since clinical characteristics, such as the proximity to the onset of motor signs [5,11,12], and different analysis procedures [13] may also account for data heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, cross-sectional and longitudinal MRI studies have suggested that structural brain changes in carriers of the HD mutation may serve as biomarkers and potentially as surrogate endpoints in clinical trials [2,3,4,5,6]. However, intact brain structure in preHD has also been reported [7,8,9,10]. It is unlikely that these discrepancies can be solely explained by differing sample sizes, since clinical characteristics, such as the proximity to the onset of motor signs [5,11,12], and different analysis procedures [13] may also account for data heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Two reports exist on increased activation in premanifest HD, which is thought to represent cortical recruitment as a compensatory strategy; this was specifically true for premanifest HD far from expected onset and not in the close to onset group. 33,34 In our view, any of these proposed explanations could be true; however, we should be extremely cautious not to overly interpret the findings because the correction for multiple comparisons reduced the number and strength of the findings. This finding could, however, lead to broader examination of MTI and other MR imaging measures in the premanifest far from disease onset group because this potentially can lead to better understanding of the neuropathology in HD.…”
Section: Discussionmentioning
confidence: 95%
“…It is now well-documented that cortical degeneration precedes clinical features, which further implicates long-term neuronal dysfunction in pathology 5,[19][20][21] . Neuronal loss, particularly in the striatum and cortex, leads to additional neurological and motor deficits 22,23 .…”
Section: List Of Figuresmentioning
confidence: 99%
“…Volumetric muscle strength changes in the upper and lower body showed highly significant, progressive increases in total group muscle strength, and significant increases for female (p<0.03) and male (p<0.02) subgroups, in all exercises after 9 months intervention (p<0.0005; Figure 40). [21], and separately for female [11] and male [10] sub-groups to indicate gender response). Highly significant increases in muscle strength were achieved for each of the above exercises after 9 months intervention (p<0.0005).…”
Section: Mean Insulin C-peptide Concentrationmentioning
confidence: 99%